The Influences of TSH Stimulation Level, Stimulated Tg Level and Tg/TSH Ratio on the Therapeutic Effect of 131I Treatment in DTC Patients - Zheng, Wei; Rui, Zhongying; Wang, Xuan; Li, Ning; Tan, Jian; Liu, Wei (Frontiers in Endocrinology, 2021)
Purpose To study the influences of pre-ablation TSH stimulation level, sTg and sTg/TSH ratio on the therapeutic effect of the first 131I treatment in DTCs. Methods According to the thyroid stimulating hormone (TSH) levels (mU/l), all the 479 differentiated thyroid cancer (DTC) patients were divided into two groups: TSH < 30 and TSH ≥ 30. The TSH ≥ 30 group was divided into three subgroups: 30 ≤ TSH < 60, 60 ≤ TSH < 90 and TSH ≥ 90. The clinical features and the therapeutic effects of the first131I treatment were analyzed. The cutoffs of stimulated thyroglobulin (sTg) and sTg/TSH ratio were calculated to predict the therapeutic effect of 131I treatment. Results Among the three subgroups, the TSH ≥ 90 subgroup was younger and less likely to be associated with cervical lymph node metastasis (LNM). The postoperative levothyroxine (L-T4) dose in the 60 ≤ TSH < 90 subgroup was the lowest. Between the two groups, patients in the TSH < 30 group had higher postoperative L-T4 dose and longer thyroid hormone withdrawal (THW) time. The excellent response rates six months after the first 131I treatment among the three subgroups and between the two groups were not of statistical significance. The distribution of different TSH stimulation levels among each response group was similar. The cutoffs for the better therapeutic effect of the first 131I treatment in sTg and sTg/TSH were < 9.51 ng/ml and < 0.11, respectively. Both univariate and multivariate logistic regressions showed that cervical LNM, distant metastasis, higher sTg and higher sTg/TSH ratio predicted poorer therapeutic effect. Conclusions There was no significant influence of TSH stimulation levels before the first 131I treatment on the therapeutic effect of DTC. The sTg/TSH ratio can be considered as another predictor of 131I therapeutic effect.